Design Conception and Simulation of Space Information Network Structure Based on Community Structure - Zhongmin PEI; Lintao REN; Wei XIONG; Zhangkai LUO (天地一体化信息网络)
Focusing on the integrated development of satellite business, based on the idea of clustering and complex network theories and methods, a design concept of space information network structure based on community structure was proposed and a virtual network with 237 nodes in 6 communities was generated with STK software.Serval static parameters such as degree distribution, betweenness, and clustering coeffi cient in the network were analyzed.The connection rules and structural characteristics of the space information network were revealed.